2010
DOI: 10.1016/j.anorl.2010.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Sclerosing polycystic adenosis of the parotid gland: Diagnosis and management

Abstract: Sclerosing polycystic adenosis of the parotid gland is a rare and recently described entity presenting several analogies to the much more frequent cystic mastitis. Although benign and well-delimited, it requires complete exeresis of the parotid, due to a non-negligible risk of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Given the yield of cells with predominantly acinar differentiation, mild nuclear abnormalities and the absence of cytologic cyst-material, the differential diagnosis of an ACC on FNAC is problematic. The difficulties pertaining to the cytological differential diagnoses of SPA have been discussed and commented on by other investigators [3,4,6,8,11]. However, in contrast to the cytological findings, the histological features of SPA are in our opinion highly characteristic.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Given the yield of cells with predominantly acinar differentiation, mild nuclear abnormalities and the absence of cytologic cyst-material, the differential diagnosis of an ACC on FNAC is problematic. The difficulties pertaining to the cytological differential diagnoses of SPA have been discussed and commented on by other investigators [3,4,6,8,11]. However, in contrast to the cytological findings, the histological features of SPA are in our opinion highly characteristic.…”
Section: Discussionmentioning
confidence: 86%
“…SPA was first described by Smith et al in 1996 in a series of 9 cases [1]. Since then just over 50 cases in a few larger series and several case reports have been published [2][3][4][5][6][7][8][9][10][11][12][13][14]. The most common site is the parotid gland with less frequent occurrence in the submandibular gland and intraoral minor salivary glands.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the seminal paper by Smith et al the largest series to date, comprising of 16 cases was published by Gnepp et al <50 cases have been published in the world English literature till date, despite the lesion being increasingly diagnosed. These cases are mostly diagnosed on histopathology and cytopathological features of SPA have been commented on in very few case reports and in only one case series …”
Section: Discussionmentioning
confidence: 99%
“…The cytopathological/fine needle aspiration (FNA) features of SPA have been characterized or commented on in seven case reports [3,4,6,8,11,17,19] and in one series (4 out of 16 patients) [5]. The investigators have reported the presence of ''syncytial epithelial ducts with apocrine changes'', oncocytic cells in a frequently ''cystic-type background'', i.e., foamy histiocytes and proteinaceous material.…”
Section: Cytopathologymentioning
confidence: 99%
“…SPA was first described by Smith et al [1] in a series comprising 9 cases. Since then, just over 50 cases in a few, mostly small series and several case reports, in a total of 19 original studies, have been published [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Apart from the seminal paper by Smith et al, the largest series to date was published by Gnepp et al [5] and comprises 16 cases.…”
Section: Introductionmentioning
confidence: 99%